A systematic approach to the management of cholestatic pruritus in primary biliary cirrhosis. Issue 3 (26th August 2015) - Hegade, Vinod S; Bolier, Ruth; Oude Elferink, Ronald PJ; Beuers, Ulrich; Kendrick, Stuart; Jones, David EJ
Abstract : Pruritus (itch) is an important symptom of primary biliary cirrhosis (PBC), an archetypal cholestatic liver disease. Cholestatic pruritus can be a debilitating symptom causing significant deterioration in patients' quality of life. Effective management of pruritus in PBC involves awareness among clinicians to adequately assess its severity, and treatment with specific drug therapies in line with current practice guidelines. In PBC, antipruritic drugs are not universally effective and/or have significant side effects, and despite best efforts with various combinations of drugs, some patients remain significantly symptomatic, eventually opting for invasive or experimental treatments. Therefore, there is a clear unmet need for better alternative treatments for patients with refractory or intractable cholestatic pruritus. Recent advances in the understanding of pathogenesis of cholestatic pruritus and bile acid physiology have raised hopes for novel therapies, some of which are currently under trial. In this review, we aim to provide a practical guide to the management of this important and complex problem, discussing current knowledge and recent advances in the pathogenesis, summarise the evidence base for available therapeutic approaches and update potential novel future therapies for the management of pruritus in PBC.